Preimplantation genetic testing for complex chromosomal rearrangements: clinical outcomes and potential risk factors - Liu, Dun; Chen, Chuangqi; Huang, Qianwen; Dong, Yunqiao; Xu, Liqing; Dong, Mei; Zhu, Zhenghong; Huang, Li; Wang, Fang; Zhang, Lijia; Zhang, Xiqian; Liu, Fenghua (Frontiers in Genetics, 2024)
Objective Complex chromosome rearrangements (CCR) are rare structural abnormalities involving at least three breakpoints, categorized into three types based on their structure: type A (three-way rearrangements), type B (double two-way translocations), and type C (exceptional CCR). However, thus far, limited data exists on preimplantation genetic testing for chromosomal structural rearrangements (PGT-SR) in CCR carriers. This study aims to evaluate the clinical outcomes and influencing factors of PGT-SR in couples with CCR. Methods Fifteen couples with unique CCR recruited from 793 couples following PGT-SR between January 2017 and May 2023. In addition, a total of 54 CCR cases, 39 previously reported as well as 15 newly added, were included in the analysis of factors associate with normal/balanced embryos. Results A total of 100 blastocysts were biopsied and analyzed in 15 CCR couples after 17 PGT-SR cycles, with 16.0% being euploid, 78.0% aneuploid and 6.0% mosaic. 11 normal/balanced embryos and one mosaic embryo were transferred, resulting in eight live births. Furthermore, based on the combined data from 54 CCR carriers, the proportion of normal/balanced embryos was 10.8%, with a significant decrease observed among female carriers compared to male heterozygotes (6.5% vs. 15.5%, p = 0.002). Type B exhibited the lowest rate of euploid embryos at only 6.7%, followed by type A at 11.6% and type C at 14.0%, although the differences were not significant (p = 0.182). After completing the multivariate generalized estimating equation (GEE) analysis, type B (p = 0.014) and female carrier (p = 0.002) were identified as independent risk factors for fewer euploid embryos. Conclusion The occurrence of balanced CCR in patients with reproductive abnormalities may be more frequent than we expected. Despite the proportion of normal/balanced embryos being significantly low, which can be influenced by CCR type and carrier’s sex, PGT-SR may improve the reproductive outcomes among CCR cases. These findings can optimize the clinical management and genetic counseling of CCR carriers seeking assisted reproductive technology (ART).